Morphological evolution of Pt-modified nanoporous gold after thermal coarsening in reductive and oxidative environments - A. A. El-Zoka (Nature Portfolio, 2020)
Abstract Nanoporous gold made by dealloying AgAuPt (NPG-Pt) has been shown to exhibit several interesting catalytic properties, tied to its exceptionally high surface area; however, structural degradation may occur owing to thermal coarsening. To understand the effect of atmosphere chemistry on thermal coarsening and degradation, and means of limiting it, this study focuses on the high-resolution characterization of NPG-Pt layers coarsened in reductive Ar-H2 atmosphere, and in oxidative air. Atom probe tomography (APT) analysis is performed on NPG-Pt, coarsened separately in either Ar-H2 or air, to characterize the atomic-scale chemical changes in the nanoligaments and to develop a mechanistic view of the inherent processes. A tendency of Ag to segregate to the surface during coarsening is found to lead to complete elimination of the nanoligament core-shell structures in both cases. Large Pt segregates form during coarsening in Ar-H2, but under the surface of the ligaments, having relatively little effect on the coarsening rate. The oxygen-induced segregation of Pt was observed to cause the inhibition of thermal coarsening after minor loss in surface area-to-volume ratio. Findings in this paper help in understanding further the thermal coarsening of heterogeneous nanomaterials made by dealloying, and the pertinent factors that come into play in different chemical environments.